Velocity-load jump testing predicts acceleration performance in elite speed skaters: But does movement specificity matter? - Zukowski, M.; Herzog, W.; Jordan, M. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose In this study, we compared the influence of movement specificity during velocity-load jump testing to predict on-ice acceleration performance in elite speed skaters.